The effect of radiotherapy, and radiotherapy combined with bisphosphonates or RANK ligand inhibitors on bone quality in bone metastases. A systematic review. Issue 2 (May 2016) - Groenen, Karlijn H.J.; Pouw, Martin H.; Hannink, Gerjon; Hosman, Allard J.F.; van der Linden, Yvette M.; Verdonschot, Nico; Tanck, Esther
Abstract: Purpose: The role of radiotherapy in stabilizing metastatic bones is unclear. This systematic review assessed the effects of (1) radiotherapy, (2) radiotherapy combined with bisphosphonates, and (3) radiotherapy combined with RANK ligand (RANKL) inhibitors on bone quality and bone strength in bone metastases originating from solid tumors. Methods: Pubmed, EMBASE and the Cochrane Library were searched. Any type of study design and type and dose of radiotherapy, bisphosphonates and RANKL inhibitors were allowed. Results: 39 articles were identified. Animal studies showed that radiotherapy had similar effects on bone quality and strength as receiving no treatment, whereas adding bisphosphonates to radiotherapy restored bone quality and strength. In patient studies, bone density increased after radiotherapy and radiotherapy combined with bisphosphonates. However, due to the often non-optimal study design and study quality, it was unclear whether this increase could be attributed to these treatments. There was insufficient evidence to assess the additional effect of bisphosphonates or RANKL inhibitors. Conclusion: Despite the clinical experience that radiotherapy is an effective treatment for bone metastases, there was no sufficient evidence for a positive effect on bone quality and fracture risk. Animal studies showed that adding bisphosphonates to radiotherapy restored bone quality and strength, whereas this was not proven in patients. There were no studies addressing the adjunct effect of RANKL inhibitors to radiotherapy. Although associated with several methodological, practical and ethical challenges, randomized controlled trials are needed.